Analisis Kasus Kapal Run Zeng 03 di Indonesia : Implementasi Prinsip Common But Differentiated Responsibilities (CBDR) dalam Illegal Fishing Lintas Negara - Siti Amalia Agustin (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Indonesia is an archipelago rich in aquatic resources that include various types of fish resources and coral reef ecosystems. However, the sustainability of these resources is increasingly threatened by the irresponsible actions of some parties, one of which is the act of Illegal Fishing. Illegal fishing is very detrimental to the country, not only damaging vulnerable fish populations, but also causing economic losses and even social impacts on society. The case of Run Zeng 03 is one of the illegal fishing cases in Indonesia, which has been fishing illegally in Indonesia's Exclusive Economic Zone since January 12, 2024. The Russian-flagged foreign vessel was arrested on May 19, 2024 in the Arafura Sea. The principle of Common But Differentiated Responsibilities (CBDR) can be applied in handling cross-border illegal fishing. The Run Zeng 03 ship itself has caused great losses to the countries in its area of operation. Whereas, the CBDR Principle emphasizes cooperation between countries to integrate in achieving common goals, despite having different responsibilities. In addition to establishing international coordination and cooperation, Indonesia itself must improve internal supervision and protection in handling these illegal fishing cases.